Reaction Kinetics of Ammonium Removal from Cow Urine by Struvite Formation Using a Baffle Column Reactor - Rizqi Rendri Anggriawan; Fauziah Hilda Alvira; Luluk Edahwati (CHEMICA: Jurnal Teknik Kimia, 2020)
Reaction kinetics is the study of reaction rates and reaction mechanisms, which refers to determining the order and reaction rate constants of a given material. This study will examine the kinetics of the reaction of ammonium removal from cow urine by struvite formation. Cow urine contains NH4 which is high enough so that it can be used as material for the manufacture of struvite. Struvite (MgNH4PO4.6H2O) is a white crystalline material consisting of magnesium, ammonium, and phosphate in equimolar. The experiment was conducted with a temperature setting of 25, 35, 45, and 65 ËšC. The flow rates used were 8.8, 11, 14.67, 22, and 44 mL/min. The process of making struvite was carried out by crystallization at pH 9, molar ratio of 3:1:1, also air rate of 0.4 L/min. The study carried out following the first order with the best conversion was 0.7797 at 8.8 ml/min and 65 ËšC. The activation energy is 3123.82 J/mol and the collision frequency is 0.0379. The equation of reaction rate k = 0.0379 e-375,73/T (K-1).